The influence of socio demographic factors on severe weather concern, knowledge and preparedness among Malaysians - Mat Said, Aini; Abu Bakar, Elistina; Ab Kadir, Mohd Zainal Abidin; Gomes, Chandima; Keul, Alexander G. (IEEE, 2014)
The objective of this study was to examine the influence of socio-demographic factors on severe weather concern, knowledge and preparedness among urban and semi-urban residents of Malaysia. Results indicated that a broad-based education approach could be used to enhance community preparedness to severe weather risks as age, education level, gender and ethnicity did not influence all the variables of the study.